DI MANA ALLAH DI TENGAH PENDERITAAN MANUSIA? (Sebuah refleksi berdasarkan Teologi Jürgen Moltmann) - Fransiskus Emanuel (Aggiornamento, 2021)
Focus of this article is on a reflection about the existence of God in the midst of human suffering. The method used by the author is a qualitative method with a literature approach and supported by the phenomenon of human suffering today, specifically related to the existence of Covid-19. The existence of a loving God and the origin of all good things is questioned in the midst of suffering. God seems to be lost, or maybe just watching the struggles of humans. Questions about God are often long reflections for believers. It is not uncommon for doubts to arise in life. The new discovery of this question based on Jürgen Moltmann's Theology of a Crucified God is that God never leaves man alone to endure their suffering. He also suffered, but His suffering was not the result of weakness or deficiencies in His existence as experienced by humans in the history of his life. He suffered from excess. That's all He does, first of all because He is Love. Love that underlies Him to sacrifice. His love strengthen man s to endure suffering.